Coming into fashion: Expanding the entrepreneurial ecosystem concept to the creative industries through a Toronto case study. (1st February 2021) - Brydges, Taylor; Pugh, Rhiannon
Abstract : This paper considers the entrepreneurial ecosystem concept, which in recent years has gained interest from a variety of perspectives including entrepreneurship, management, and economic geography. Specifically, the paper identifies a gap in the literature regarding the concept's sectoral or industrial focus. Prior applications to real‐world case studies have focused on a fairly narrow range of industries and places. In this paper, we apply the concept to a case study of one creative and cultural industry, the fashion industry, to help us understand not only the performance and function of entrepreneurs and small businesses in this industries, but also potential policy supports. We map the institutions and spaces in Toronto's entrepreneurial ecosystem, drawing on extensive qualitative research to consider the dynamics and interactions therein. In parallel, we advance the concept theoretically, questioning its tenability and applicability in a wider range of economic systems by adding the perspective of cultural and creative industries. Key Messages: The entrepreneurial ecosystem (EE) framework provides the foundation for an analysis of the institutions, actors, and organizations within the Toronto fashion industry. We found a fragmented, competitive EE composed of overlapping institutions and isolated fashion designers. There is a need for EE research to move beyond successful, high‐tech and/or masculinized cases to consider a broader range of entrepreneurial spaces and actors. Devenir à la mode: étendre le concept d'écosystème entrepreneurial aux industries créatrices à travers une étude de cas à Toronto: Cet article étudie le concept d'écosystème entrepreneurial qui, au cours des dernières années, a suscité de l'intérêt dans différents domaines, y compris l'entrepreneuriat, l'administration et la géographie économique. La présente recherche relève plus particulièrement une lacune dans la littérature concernant le pivot industriel ou sectoriel du concept. Les études de cas antérieures ont mis l'accent sur un éventail relativement étroit d'industries et de territoires. Pour notre part, nous appliquons le concept à une industrie culturelle et créatrice, c'est‐à‐dire l'industrie de la mode, pour nous aider à comprendre non seulement le rendement et la fonction des entrepreneurs et des petites entreprises dans ces industries, mais également les appuis politiques potentiels. De plus, nous cartographions les institutions et les espaces dans l'écosystème entrepreneurial de Toronto en nous inspirant d'une recherche qualitative approfondie afin d'examiner la dynamique et les interactions que l'on y retrouve. Parallèlement à ces démarches, nous approfondissons le concept sur le plan théorique, remettant en question sa validité et son applicabilité à un éventail plus large de systèmes économiques, par l'intermédiaire de l'exemple des industries culturelles et créatrices .